Crisis Fatigue in the Digital Age: How Constant Exposure to Disasters Affects Public Attention and Engagement - Uri Samet, BA, MPH (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This review article examines the pervasive phenomenon of crisis fatigue in the contemporary digital age, analyzing how relentless exposure to global crises through online platforms impacts public attention and engagement. Drawing upon a comprehensive review of extant literature, this paper delineates the psychological and physiological manifestations of crisis fatigue, distinguishing it from related constructs such as compassion fatigue. The analysis highlights how the unique characteristics of the digital ecosystem, including information overload, cognitive strain, algorithmic amplification of distressing content, and the emerging influence of artificial intelligence (AI), serve as amplifiers of this fatigue. Furthermore, the article explores the psychological mechanisms underlying public disengagement, such as desensitization, the moral repetition effect, compassion collapse, and learned helplessness. The consequences of crisis fatigue on societies are then discussed, focusing on declining public and political participation and the significant challenges posed to humanitarian aid and disaster management efforts. The central argument proposes that the continuous, high-volume, and often sensationalized delivery of crisis information online reduces individuals' capacity for sustained attention and emotional care, thereby limiting effective public and political response.